Pulse pressure in children and adolescents with type 1 diabetes mellitus in Germany and Austria. Issue 3 (28th October 2013) - Dost, Axel; Molz, Esther; Krebs, Andreas; Bechtold, Susanne; Kapellen, Thomas; Rohrer, Tilman; Raile, Klemens; Fritsch, Maria; Schwab, Karl Otfried; Holl, Reinhard
Abstract Background Impaired blood pressure regulation contributes to the development of diabetic complications. The influence of systolic (SBP) vs. diastolic blood pressure (DBP) is still controversial. Peripheral pulse pressure (PP), the difference between SBP and DBP, is an indicator for arterial stiffness. Only little data are available for PP in children. Therefore, we studied PP regulation in type 1 diabetic children and adolescents. Methods Blood pressure values of 46 737 patients with T1DM younger than 20 years are documented in the DPV database and were compared with the control populations of the '4th report on high blood pressure (4th report)' and the German KIGGS study. Results PP is increased in 63% (4th report) or 67% (KIGGS) of the patients, respectively. The rate of increased PP remains stable between 59 and 68%, irrespective of sex, age, and the control population. Absolute PP is elevated independently of the control population (PP T1DM 49.13 ± 11.1 vs. 4th report 45.38 ± 3 vs. KIGGS 44.58 ± 4.6 mmHg; all p < 0.0001, Wilcoxon test) and increases with age in both sexes. Age, male sex, diabetes duration, insulin dose, and body mass index (BMI) are independent factors contributing to elevated absolute PP levels and to the prevalence of wide PP. HbA1c is negligible negatively related to increased PP levels (multiple linear regression). Conclusions In T1DM increased PP is a marker for accelerated arterial stiffness and aging and should be considered as an additional risk factor in the treatment of diabetic children. Elevated PP in children with T1DM may contribute to the high risk for early development of atherosclerosis.